Case Series of Brittle Cornea Syndrome. (20th March 2020) - Eleiwa, Taher; Raheem, Mariam; Patel, Nimesh A.; Berrocal, Audina M.; Grajewski, Alana; Abou Shousha, Mohamed
Abstract : Purpose . This case series demonstrate diagnostic features, treatment options, and challenges for Brittle Cornea Syndrome. Observations . Three cases presented with bluish sclera and extremely thin cornea. Genetic workup was performed and confirmed the diagnosis of Brittle Cornea Syndrome, a rare autosomal recessive disorder characterized by corneal thinning and blue sclera. Case 1 was a 4-year-old boy who developed cataract and glaucoma after undergoing right tectonic penetrating keratoplasty (PK) secondary to a spontaneous corneal rupture. Glaucoma was controlled medically. Later, the kid underwent right transcorneal lensectomy and vitrectomy with synechiolysis. After 6 weeks, he sustained graft dehiscence that was repaired using onlay patch graft. Case 2 was a 7-year-old boy who underwent PK in the right eye, then a pericardial patch graft in the left eye following spontaneous corneal rupture. Glaucoma in both eyes was controlled medically. Case 3 was the 2-year-old sister of the 2 nd case. She had a pachymetry of 238  μ m OD and 254  μ m OS. In the 3 cases, parents were instructed to take protective measures for both eyes and to continue with follow-up visits. Also, they were instructed to have regular screenings for late-onset hearing loss, dental abnormalities, and bone deformities. Conclusions . Long-term follow-up of children diagnosed with Brittle Cornea Syndrome is paramount to minimize the morbidity of corneal rupture and late-onset extraocular conditions.